High Molecular Weight Kininogen Deficiency: a Patient who Underwent Cardiac Surgery - Davidson, S. J.; Burman, J. F.; Rutherford, L. C.; Keogh, B. F.; Yacoub, M. H. (Thrombosis and Haemostasis, 2001)
A 66 year old male, referred for cardiac surgery, was found to have high molecular weight kininogen deficiency (activity <1%). Apart from activated partial thromboplastin time (APTT) >300 s, tests of haemostasis were otherwise normal (factors VIII, IX, XI, XII and prekallikrein). No inhibitor of coagulation was found.The activated coagulation time (ACT) was 800 s pre-operatively and >1000 s after heparin. Heparin levels were measured directly by an anti-Xa chromogenic assay, with values of between 2.9 and 3.2 u/ml during cardiopulmonary bypass. Thrombin-antithrombin levels rose from 2.3*g/l before surgery to a peak of 83.5*g/l at the end of cardio-pulmonary bypass. Cross linked fibrin d-dimers (XDP) levels rose from 100 ng/ml before operation to 600 ng/ml after protamine administration. The patient had no excess bleeding and no thrombotic complications from surgery.This patient shows that high molecular weight kininogen is not required for thrombin formation or fibrinolysis during cardiac surgery and illustrates the need to measure heparin directly in patients with such contact factor deficiencies.
Keywords: High molecular weight kininogen; cardiopulmonary bypass; thrombin; fibrinolysis